Study on Cross-cultural Adaptation of Expatriates: A Case of GJWJ in India - Wu, Yiming (Advances in Social Sciences Research Journal, 2022)
As the world's leading and largest producer of stationery metal parts, GJWJ has entered India for more than 20 years and occupies more than 70% of the Indian stationery manufacturing market. This paper takes the expatriates of GJWJ in India as the research object to identify the problems of cross-cultural adaptation of these expatriates and explore some influencing factors through questionnaires and interviews. It is found that expatriates’ education, work experience, English proficiency, social support, social contact and religious factor are all related to psychological adaptation and sociocultural adaptation;among these related factors, expatriates’ education, work experience, English proficiency and religious factor have significant influence and predictive effect on cross-cultural adaptation;there are some problems of expatriates in cross-cultural adaptation during the assignment, such as problems in psychological adaptation, in religious beliefs, in cross-cultural training, in cultural integration, in work management and in social support.